Hypermucinous, Goblet Cell-Deficient and Crypt Cell Dysplasias in Inflammatory Bowel Disease are Often Associated with Flat/Invisible Endoscopic Appearance and Advanced Neoplasia on Follow-Up. (7th July 2021) - Choi, Won-Tak; Salomao, Marcela; Zhao, Lei; Alpert, Lindsay; Setia, Namrata; Liao, Xiaoyan; Drage, Michael G; Westerhoff, Maria; Cheng, Jerome; Lauwers, Gregory Y; Ko, Huaibin Mabel
Abstract: Background and Aims: Several different types of non-conventional dysplasia have been recently described in inflammatory bowel disease [IBD]. Hypermucinous, goblet cell-deficient and crypt cell dysplasias have received most attention, but there is limited information regarding their clinicopathological features and clinical outcomes. Methods: A total of 126 cases of hypermucinous [ n = 55], goblet cell-deficient [ n = 26] and crypt cell [ n = 45] dysplasias from 97 IBD patients were collected from seven different institutions and analysed. Results: The cohort included 62 [64%] men and 35 [36%] women with a mean age of 49 years [range: 20–78]. The majority of affected patients had longstanding IBD [mean duration: 18 years]. Nineteen [20%] patients had a concurrent history of primary sclerosing cholangitis. As a group, non-conventional dysplasia was predominantly found in patients with ulcerative colitis [UC] [ n = 68; 70%] and occurred in the left colon [ n = 80; 63%]; however, hypermucinous dysplasia [57%] was the least frequently associated with UC compared with goblet cell-deficient [74%] and crypt cell [89%] dysplasias [ p = 0.016]. Fifty [52%] patients had a history of conventional dysplasia, detected in the same colonic segment as non-conventional dysplasia at a rate of 33%. Goblet cell-deficient dysplasia [74%] was more frequently associated with conventional dysplasia than hypermucinous [43%] and crypt cell [48%] dysplasias [ p = 0.044]. While hypermucinous dysplasia often had a polypoid appearance [58%], crypt cell [96%] and goblet cell-deficient [65%] dysplasias were more likely to present as flat/invisible lesions [ p < 0.001]. Most lesions were low-grade [87%] at diagnosis, but goblet cell-deficient dysplasia [31%] more often showed high-grade dysplasia [HGD] compared with hypermucinous [15%] and crypt cell [0%] dysplasias [ p = 0.003]. Hypermucinous dysplasia usually demonstrated a tubulovillous/villous architecture [76%], whereas goblet cell-deficient dysplasia was predominantly tubular [92%]. A flat architecture was exclusively associated with crypt cell dysplasia [100%] [ p < 0.001]. Immunohistochemical stain results for p53 were available for 33 lesions; 14 [42%] showed strong [3+] and patchy [10–50%] to diffuse [>50%] nuclear overexpression or null staining pattern, including four [33%] of 12 hypermucinous, two [29%] of seven goblet cell-deficient and eight [57%] of 14 crypt cell dysplastic lesions [ p = 0.726]. Follow-up biopsies or resections were available for 92 low-grade lesions from 71 patients; 55 [60%] lesions, including 19 [49%] of 39 hypermucinous, 10 [59%] of 17 goblet cell-deficient and 26 [72%] of 36 crypt cell dysplastic lesions [ p = 0.116], were associated with subsequent detection of HGD [ n = 34; 37%] or adenocarcinoma [ n = 21; 23%] at the site of previous biopsy or in the same colonic segment within a mean follow-up time of 12 months [range: <1–73]. Conclusions: Hypermucinous, goblet cell-deficient and crypt cell dysplasias have distinct clinicopathological features but appear to have a similar high risk of association with advanced neoplasia [HGD or adenocarcinoma]. More than half of the lesions [66%] presented as flat/invisible dysplasia, suggesting that IBD patients may benefit from random biopsy sampling in addition to targeted biopsies. Although not uncommonly associated with conventional dysplasia, non-conventional dysplasia may be the only dysplastic subtype identified in IBD patients. Therefore, it is important to recognize these non-conventional subtypes and recommend complete removal and/or careful examination and follow-up. Graphical Abstract: